"Lost and Found": snoRNA Annotation in the Xenopus Genome and Implications for Evolutionary Studies. (6th September 2019) - Deryusheva, Svetlana; Talhouarne, Gaëlle J S; Gall, Joseph G
Abstract: Small nucleolar RNAs (snoRNAs) function primarily as guide RNAs for posttranscriptional modification of rRNAs and spliceosomal snRNAs, both of which are functionally important and evolutionarily conserved molecules. It is commonly believed that snoRNAs and the modifications they mediate are highly conserved across species. However, most relevant data on snoRNA annotation and RNA modification are limited to studies on human and yeast. Here, we used RNA-sequencing data from the giant oocyte nucleus of the frog Xenopus tropicalis to annotate a nearly complete set of snoRNAs. We compared the frog data with snoRNA sets from human and other vertebrate genomes, including mammals, birds, reptiles, and fish. We identified many Xenopus- specific (or nonhuman) snoRNAs and Xenopus -specific domains in snoRNAs from conserved RNA families. We predicted that some of these nonhuman snoRNAs and domains mediate modifications at unexpected positions in rRNAs and snRNAs. These modifications were mapped as predicted when RNA modification assays were applied to RNA from nine vertebrate species: frogs X. tropicalis and X. laevis, newt Notophthalmus viridescens, axolotl Ambystoma mexicanum, whiptail lizard Aspidoscelis neomexicana, zebrafish Danio rerio, chicken, mouse, and human. This analysis revealed that only a subset of RNA modifications is evolutionarily conserved and that modification patterns may vary even between closely related species. We speculate that each functional domain in snoRNAs (half of an snoRNA) may evolve independently and shuffle between different snoRNAs.